2007
DOI: 10.1080/15563650600956329
|View full text |Cite
|
Sign up to set email alerts
|

Methanol mass poisoning in Estonia: Outbreak in 154 patients

Abstract: Given limited resources, triage and use age of tertiary care centers allowed a small community hospital to treat a high number of methanol-poisoned patients. Critical resources were ventilators and dialyzing machines, whereas stores of antidote (ethanol) and bicarbonate were sufficient. Many patients were mechanically ventilated by hand and treated with bicarbonate and ethanol during transport to tertiary care centers for hemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
139
3
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(161 citation statements)
references
References 16 publications
7
139
3
2
Order By: Relevance
“…Visual disturbances, including decreased visual acuity, photophobia, and blurred vision, and abdominal pain are the most common symptoms of methanol intoxication (7,64), one or both being found in 37 to 72% of patients (7,64). Hyperemia of the optic disks and a reduced papillary response to light may be present.…”
Section: Clinical Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Visual disturbances, including decreased visual acuity, photophobia, and blurred vision, and abdominal pain are the most common symptoms of methanol intoxication (7,64), one or both being found in 37 to 72% of patients (7,64). Hyperemia of the optic disks and a reduced papillary response to light may be present.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…The severity of the visual abnormalities is directly correlated with the severity of the metabolic acidosis (6,7,12). Although most patients will recover normal visual function, permanent impairment of vision has been observed in from 11 to 18% of patients (7,64). Abdominal pain can be present in both the presence and the absence of pancreatitis (7,12).…”
Section: Clinical Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test this hypothesis, the affinity of abacavir for ADH in comparison with methanol should firstly be experimentally determined and if it is shown that it has a greater affinity for ADH compared with methanol, a multicenter randomized controlled trial study should be designed to compare fomepizole with abacavir in the treatment of methanol-poisoned patients. Albeit, the best opportunities for conducting this study are the mass poisonings with methanol that regularly occur in developed and developing countries [9,[18][19][20][21].…”
mentioning
confidence: 99%
“…In contrary, methanol poisoning is a rare toxicity that is seen in the form of isolated episodes and intentional ingestion, and sometimes occurs as single epidemies [9,[18][19][20][21]. Therefore, fomepizole is not widely stocked in some hospital pharmacy stocks in comparison…”
mentioning
confidence: 99%